A child with vitiligo - Prylińska, Monika; Marcin Kożuchowski; Jakub Husejko (Journal of Education, Health and Sport, 2021)
Vitiligo is a chronic skin condition which affects 0,5-2% of the world’s population, without any sex or ethnical predilection. Clinically it is characterized by the development of well-defined depigmented macules. Although its etiopathogenesis is exquisitely compound and remains not fully anderstood, it is known that it results from the destruction of melanocytes present in the skin. The aim of this paper is to present vitiligo clinical picture in a children population, its etiopathogenesis and available therapeutical methods. There are many therapeutic options for vitiligo, none of which is fully effective, hence appropriate patients education concerning various medical and cosmetic therapies, as well as the psychological aspects of the disease, is extremely important.